2014
DOI: 10.1111/jcpt.12155
|View full text |Cite
|
Sign up to set email alerts
|

Genetic selection of volunteers and concomitant dose adjustment leads to comparable hydralazine/valproate exposure

Abstract: Comparable hydralazine exposures (differences in AUC0-inf of only 7%) were observed in this study with genetic selection of volunteers and concomitant dose adjustment. However, the conclusions have yet to be confirmed with a full-powered 2 × 2 crossover study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 52 publications
(102 reference statements)
2
4
0
Order By: Relevance
“…In previous in vitro metabolic experiments using SMZ as a substrate, NAT2 * 5, * 6, and * 7 showed lower Vmax values than that of NAT2 * 4, but only NAT2 * 7 showed higher affinity for SMZ with lower Km compared with NAT2 * 4 (Olivera et al, 2007;Garces-Eisele et al, 2014), consistent with our current study. Additionally, NAT2 * 5 and * 6 alleles result in lower N-acetyltransferase activities toward SMZ compared with NAT2 * 7 (Walraven et al, 2008), and carriers of NAT2 * 5 and * 6 were categorized as USAs in the current study.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In previous in vitro metabolic experiments using SMZ as a substrate, NAT2 * 5, * 6, and * 7 showed lower Vmax values than that of NAT2 * 4, but only NAT2 * 7 showed higher affinity for SMZ with lower Km compared with NAT2 * 4 (Olivera et al, 2007;Garces-Eisele et al, 2014), consistent with our current study. Additionally, NAT2 * 5 and * 6 alleles result in lower N-acetyltransferase activities toward SMZ compared with NAT2 * 7 (Walraven et al, 2008), and carriers of NAT2 * 5 and * 6 were categorized as USAs in the current study.…”
Section: Discussionsupporting
confidence: 91%
“…Our study showed that genotypes could be categorized into the USA phenotype in N-acetylation of HLZ, PZ, and SMZ by hierarchical clustering analysis. In a previous work, the pharmacokinetics of oral HLZ were found to be dependent on the NAT2 genotype during pregnancy (Han et al, 2019), and SA status was shown to be associated with clinical blood pressure and 24-h blood pressure after HLZ treatment in patients with resistant hypertension (Garces-Eisele et al, 2014). Therefore, the * 6/ * 6, * 6/ * 7, and * 7/ * 7 genotypes must be clearly distinct from the SA group, and this categorization may further improve individualization of HLZ treatment.…”
Section: Discussionmentioning
confidence: 94%
“…The three studies above suggest that evidence supports an association between acetylator phenotype or genotype and hydralazine concentrations. Similar findings were observed in other populations: Asian, African American, British, Kenyan, Mexican, Native Hawaiian, and Pacific Islanders (Table 2) [50-60]. Thus, a consistent and significant relationship between acetylator status and hydralazine concentration exists across a spectrum of populations.…”
Section: Effects Of Predicted Nat2 Activity On Hydralazine Concentratsupporting
confidence: 84%
“…We explored gestational age, body weight, demographics, baseline hemodynamics, and concomitant medication dosage, but did not find an explanation for this unexpected finding. A study in healthy nonpregnant volunteers demonstrated that higher hydralazine dose was needed for NAT2 rapid acetylators to achieve comparable hydralazine AUC, as with the slow acetylators . A large study in nonpregnant subjects showed that rapid acetylators did not achieve adequate therapeutic effect with oral hydralazine, suggesting that NAT2 acetylation status might be important in pharmacodynamic response to oral hydralazine .…”
Section: Discussionmentioning
confidence: 99%